Leadership Criteria in Islam and its Benefit: Muslim Involvement in Non-Muslim Goverments - Makhsus, Makhsus; Hayati, Ilda; Fatarib, Husnul; Saharuddin, Desmadi (Al-Adyan: Journal of Religious Studies, 2020)
Basically, a Muslim does not leave the Muslim community, but with the development of Islam many problems occur. The departure of the Prophet Yusuf from the Muslim community has been described in the Qur'an. He served various maturity processes under the guidance of Allah al-Mighty. The figure of the Prophet Yusuf has been depicted and immortalized as a shadow ruler who officially served as minister of finance, agriculture and head of the logistics affairs agency. The question arises whether a Muslim can become a non-Muslim leader who will later be neglected and will have a negative impact on the faith and syari'ah carried out by Muslim leaders who control non-Muslim governments. With literature study and content analysis approach, the writer describes the literature qualitatively about the status of Muslims who are in the midst of non-Muslims and vice versa, to dismiss the opinion of good kafirs who are more worthy of being leaders than evil and corrupt Muslims. A Muslim can become a leader in the midst of non-Muslims for the benefit and preaching of Islam as was done by the Prophet Yusuf A.S, who proved himself clean after leaving prison. The criteria for a leader in Islam are flexible enough that sometimes a Muslim who is not consistent with sharia rules can sometimes bring great benefits to Muslims. Not only that, many Muslim leaders who were very instrumental in protecting Muslims and spreading Islam in Russia such as Berke Khan have deployed infidel armies to protect Muslims from destruction.Pada dasarnya seorang muslim tidak meninggalkan komunitas muslimnya, akan tetapi seiring perkembangan islam banyak masalah yang muncul. Hengkangnya Nabi Yusuf dari komunitas Muslim telah dijelaskan dalam Alquran.  Dia menjalani berbagai proses pendewasaan di bawah bimbingan Allah swt. Sosok Nabi Yusuf telah digambarkan dan diabadikan sebagai penguasa bayangan yang resmi menjabat sebagai menteri keuangan, pertanian, dan kepala badan logistik.  Timbul pertanyaan apakah seorang Muslim bisa menjadi pemimpin non-Muslim yang nantinya akan terabaikan dan berdampak negatif pada keimanan dan syari'at yang diemban oleh tokoh Muslim yang menguasai pemerintahan non-Muslim.  Dengan pendekatan studi pustaka dan analisis isi, penulis mendeskripsikan literatur secara kualitatif tentang status umat Islam yang berada di tengah-tengah non-Muslim dan sebaliknya, untuk menepis pendapat seorang kafir yang baik lebih layak menjadi pemimpin daripada seorang Muslim yang jahat dan korup.  Seorang Muslim bisa menjadi pemimpin di tengah-tengah non-Muslim untuk kemaslahatan dan dakwah Islam seperti yang dilakukan oleh Nabi Yusuf A.S yang membuktikan dirinya bersih setelah keluar dari penjara. Kriteria seorang pemimpin dalam Islam cukup fleksibel sehingga terkadang seorang Muslim yang tidak konsisten dengan aturan syariah dapat membawa manfaat yang besar bagi umat Islam. Tidak hanya itu, banyak pemimpin Muslim yang sangat berjasa dalam melindungi umat Islam dan menyebarkan Islam di Rusia seperti Berke Khan yang telah mengerahkan pasukan kafir untuk melindungi umat Islam dari kehancuran.